It's a MALDI but it's a goodie: MALDI-TOF mass spectrometry for microbial identification. Issue 8 (29th April 2014) - Randell, Paul
Abstract : The last few years have witnessed a revolution in the diagnostic microbiology laboratory with the emergence of matrix assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS) as an indispensible tool in microbial identification. In many laboratories this has superseded biochemical profiling. A mass spectrum is acquired from an unknown micro-organism and this proteomic fingerprint is then compared with a database of reference spectra to ascertain the likely genus and species identity. The reproducibility of this method is facilitated by the analysis of continually produced, highly abundant proteins (mainly ribosomal proteins) in the mass range 2000 to 20 000 Da. MALDI-TOF MS is reliable and rapid and has the ability to determine the identity of an isolate from culture in a matter of minutes rather than the hours or days required by more traditional methods. In addition to microbial identification of cultured isolates, work is underway to extend the utility of MALDI-TOF MS to include bacterial identification directly from clinical samples as well as providing timely information regarding antibiotic resistance and typing of different micro-organisms.